2021
DOI: 10.1002/adfm.202107992
|View full text |Cite
|
Sign up to set email alerts
|

Design of p‐WSe2/n‐Ge Heterojunctions for High‐Speed Broadband Photodetectors

Abstract: Van der Waals (vdW) 2D/3D heterostructures are extensively studied for high-performance photodetector applications. Until now, the type of 2D materials has been the primary area of interest rather than the design of 3D semiconductors. In this study, high-speed broadband photodiodes (PDs) based on vdW p-WSe 2 /n-Ge heterojunctions are reported, and the performance compared with different n-Ge regions formed via the ion-implantation process. The fabricated PD with a typical long n-Ge region and low doping concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 41 publications
0
30
0
Order By: Relevance
“…Therefore, high-speed PDs with ultrawide wavelength operation are highly desired. In recent years, some results have been demonstrated toward this direction, such as GeSn PDs, [11,260] all Si PDs, [13] 2D material-based PDs [224,261] as well as Ge PDs in combination with perovskite material. [254] However, device performance in these reports is typically far from that of PDs working in the usual O/C bands.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, high-speed PDs with ultrawide wavelength operation are highly desired. In recent years, some results have been demonstrated toward this direction, such as GeSn PDs, [11,260] all Si PDs, [13] 2D material-based PDs [224,261] as well as Ge PDs in combination with perovskite material. [254] However, device performance in these reports is typically far from that of PDs working in the usual O/C bands.…”
Section: Discussionmentioning
confidence: 99%
“…where ε 1 and ε 2 are the dielectric constants of WSe 2 and Ge (Ga 2 O 3 ), respectively; N d is the doping concentration of Ge (Ga 2 O 3 ); and N a is the doping concentration of WSe 2 . [19] The depletion widths of the x n under zero bias were calculated as 377 nm for Ge and 40 nm for Ga 2 O 3 , and the corresponding depletion widths of WSe 2 (x p ) were 10 and 67 nm, respectively. The calculation results showed that WSe 2 was fully depleted by the DHJ.…”
Section: Electrical and Photoresponse Characteristicsmentioning
confidence: 99%
“…Moreover, optimized Ge design via the ion-implantation process shows great potential for high-speed broadband photodetectors that can be integrated with CMOS designs and processes. [15][16][17][18][19] A vdW 2D/Ge heterostructure with enhanced responsivity in the SWIR range (>1550 nm), while maintaining a relatively simple two-terminal diode configuration, can be pivotal for photodetectors. To achieve improvement, photogenerated carriers can be multiplied via an additional layer on top of the 2D/Ge junction (i.e., double heterojunction, DHJ), resulting in a complicated device configuration with dual bias polarity operations.…”
mentioning
confidence: 99%
“…To fabricate PDs with broad spectral responses, several methods have been proposed. Through material integration and surface texturing, broad-spectrum PDs have been obtained. ,, In addition, applying the downshifting effect by adding a layer of fluorescent materials to fabricate integrated devices is one of the most common and effective means of solving technical difficulties in UV–vis band detection. In recent years, due to their excellent optoelectronic properties and huge material family system, perovskites have been rapidly developed in many optoelectronic fields, such as photovoltaics, light emission, photodetection, , etc .…”
Section: Introductionmentioning
confidence: 99%